Role of Probiotics in Halitosis of Oral Origin: A Systematic Review and Meta-Analysis of Randomized Clinical Studies - López-Valverde, Nansi; López-Valverde, Antonio; Macedo de Sousa, Bruno; Rodríguez, Cinthia; Suárez, Ana; Aragoneses, Juan Manuel (Frontiers in Nutrition, 2022)
Halitosis or oral malodor is a condition caused by the putrefaction of sulfur-containing amino acids. It affects 30-50% of the population and causes social rejection, reducing quality of life and self-esteem. Probiotics, especially Lactobacillus species, have been proposed for the treatment of genuine halitosis, due to their ability to reduce bacterial colonization. Our objective was to evaluate their use for the treatment of oral halitosis. Applying the PRISMA statement guidelines, we searched PubMed, EMBASE and Web of Science databases for scientific articles from the last 15 years, up to July 2021. The keywords used were ‘Probiotics’; ‘Halitosis’; ‘Mouth diseases’; ‘Oral health’; ‘Humans’; ‘Randomized Clinical Trials’ according to the question, ‘Are probiotics effective for the reduction or elimination of oral halitosis?’. Fourteen studies were identified, although only 4 met the inclusion criteria. We evaluated 283 participants treated with 2 different probiotics, with a follow-up of at least 2 weeks. Risk of bias was assessed using the Cochrane Collaboration tool. A fixed-effects meta-analysis was performed. No statistical significance was found (p=0.53). Despite the limitations of this meta-analysis, we believe that some probiotics have a beneficial effect on halitosis, although more clinical trials are needed to establish real evidence on this aspect.